2005
DOI: 10.1172/jci23378
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for the kidney and systemic tissues in blood pressure regulation by the renin-angiotensin system

Abstract: Angiotensin II, acting through type 1 angiotensin (AT 1 ) receptors, has potent effects that alter renal excretory mechanisms. Control of sodium excretion by the kidney has been suggested to be the critical mechanism for blood pressure regulation by the renin-angiotensin system (RAS). However, since AT 1 receptors are ubiquitously expressed, precisely dissecting their physiological actions in individual tissue compartments including the kidney with conventional pharmacological or gene targeting experiments has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
115
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 275 publications
(123 citation statements)
references
References 46 publications
7
115
1
Order By: Relevance
“…Our previous studies using kidney cross-transplantation showed that AT 1A receptors within the kidney are crucial for regulation of blood pressure 4 and for the development of hypertension 5 . Within the kidney, AT 1 receptors are broadly expressed by epithelial cells across the nephron where they have been shown to have potent influence on sodium reabsorption 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies using kidney cross-transplantation showed that AT 1A receptors within the kidney are crucial for regulation of blood pressure 4 and for the development of hypertension 5 . Within the kidney, AT 1 receptors are broadly expressed by epithelial cells across the nephron where they have been shown to have potent influence on sodium reabsorption 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The major effector peptide of the RAS, angiotensin II (Ang II), is generated by sequential cleavage of the substrate angiotensinogen and acts via the angiotensin type 1 (AT 1 ) receptor to increase blood pressure 2, 3 . Studies from our laboratory using kidney cross-transplantation have demonstrated the critical role of AT 1 receptors inside the kidney to control blood pressure 4 and to promote hypertension 5 . In the kidney, AT 1 receptors are ubiquitously expressed in glomeruli, vascular and renal epithelia 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II (ANG II) is the main active peptide of the renin-angiotensin system and plays a prominent role in maintaining blood pressure and body fluid and electrolyte balance homeostasis [2]. Dopamine (DA) and ANG II exhibit opposed physiological effects.…”
Section: Introductionmentioning
confidence: 99%
“…4 Among them, the kidneys have been demonstrated to play a vital role in the development of hypertension in both humans and experimental animal models. 5,6 Kidneys transplanted from hypertensive donors increase BP in normotensive recipients, whereas kidneys transplanted from normotensive donors lower BP in hypertensive recipients both in clinical 710 and experimental renal transplantation studies. 1114 …”
Section: Introductionmentioning
confidence: 99%